Pemikiran Linguistik Sibawaih (147-180 H) dan Urgensinya bagi Studi Islam - Arif Al-Wasim (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
Mastering the structural linguistics of Arabic is the main keys to understand the Quran and Hadith. Sibawaih (147-180 H) is an Islamic thinkers who had a role in build the structural linguistic foundation of Arabic. This research aims to explore Sibawaih's classical structural linguistic thinking and its urgency for the development of Islamic studies. This research is a library research presented descriptively. The primary source is al-Kitab written by Sibawaih, while the secondary data is the other supporting data. The results showed that the nahwu codified by Sibawaih was integration among nahwu, bayan, and literature. Sibawaih used the authoritative method: sima'i and qiyasi in compiling nahwu. When explaining the grammatical structure, Sibawaih has not given the specific terminology in defining. Instead, he has discussed the procedures in placing the word in a sentence in detail. Sibawaih’s efforts have rationalized and completing the Arabic. His effort can be considered as an attempt to form a category of causality.